2020
DOI: 10.3390/app10207201
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Classification Approaches for Breast Cancer Identification via MRI: State-Of-The-Art and Vision for the Future

Abstract: Mining algorithms for Dynamic Contrast Enhanced Magnetic Resonance Imaging (DCE-MRI) of breast tissue are discussed. The algorithms are based on recent advances in multi-dimensional signal processing and aim to advance current state-of-the-art computer-aided detection and analysis of breast tumours when these are observed at various states of development. The topics discussed include image feature extraction, information fusion using radiomics, multi-parametric computer-aided classification and diagnosis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…First, medical image processing requires extremely high accuracy for disease diagnosis [18][19][20][21][22][23]. Segmentation in medical imaging refers to pixel-level or voxel-level segmentation.…”
Section: Existing Challengesmentioning
confidence: 99%
“…First, medical image processing requires extremely high accuracy for disease diagnosis [18][19][20][21][22][23]. Segmentation in medical imaging refers to pixel-level or voxel-level segmentation.…”
Section: Existing Challengesmentioning
confidence: 99%
“…The current study is also subject to some limitations, such as the way to select target regions based on contextual information and weights, to capture the spatial and channel correlations among features [39][40][41], to strengthen information exchange between the spatial and channel features, and to enhance the original features of small targets [42,43] to improve the classification performance of imaged tumors. Especially, further exploration should be conducted on the way to achieve the extraction of boundary features by using the local density deviation of adjacent targets as a reference item.…”
Section: Discussionmentioning
confidence: 99%
“…Taking DCE-MRI as an example, it is reported that DCE-MRIs can be divided into several different representative feature regions according to a certain threshold, and texture features are calculated in these regions to measure the heterogeneity degree of these regions [ 77 , 81 , 82 ]. An increasing number of sophisticated methods cluster similar dynamic enhancement patterns [ 13 , 83 , 84 ] and describe the heterogeneity of vascular characteristics in tumor spaces through DCE-MRIs. But technically, the current stage of tumor heterogeneity analysis is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%